A study of the Social Model of The Korean Welfare State (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study1 is an exploratory study to identify the characteristics and level of Korean Welfare state. In order to clarify the characteristics of the welfare state in Korea, a social model that explains the development of the welfare state was applied and various social indicators in the social welfare sector of OECD countries were used to categorize it. To achieve the purpose of this study, cluster analysis was used as a research method and the most recent OECD data were used. For this, SPSS version 20 and AMOS 21 were used. As a result OECD countries were classified into five types, and Korea was included as an underdeveloped welfare state along with Mexico and Chile, despite its enormous economy. The implications of this study show that the Korean government should expand social welfare institutions and services to suit the current economic level.